Psychotherapeutic Interventions for Anxiety Disorders: A Narrative Review of Mechanisms, Efficacy, and Implementation Barriers - Moin, Saman; Trivedi, Neelanchal (Journal of Pharmacy Practice and Community Medicine, 2026)
The disorders of Anxiety represent the most prevalent class of mental health conditions globally and are associated with substantial functional impairment, economic burden, and reduced quality of life. Although pharmacotherapy remains widely used, psychotherapy has emerged as a cornerstone of evidence-based treatment, particularly for long-term symptom management and relapse prevention. This review aims to comprehensively examine psychotherapeutic approaches for anxiety disorders, their mechanisms of action, comparative effectiveness with pharmacotherapy, implementation barriers, and emerging future directions. A narrative review of contemporary literature was conducted, synthesizing findings from meta-analyses, randomized controlled trials, neurobiological research, and global mental health implementation studies. Cognitive Behavioral Therapy (CBT) demonstrates the strongest and most consistent empirical support across anxiety disorders, with moderate to large effect sizes and durable treatment outcomes. Exposure-based interventions operate through inhibitory learning mechanisms, while third-wave therapies such as Acceptance and Commitment Therapy (ACT) enhance psychological flexibility and emotional regulation. Neuroimaging studies indicate that psychotherapy modulates amygdala hyperactivity and strengthens prefrontal regulatory networks. Compared to pharmacotherapy, psychotherapy shows comparable short-term efficacy and superior long-term relapse prevention. However, substantial global treatment gaps persist due to stigma, limited workforce capacity, structural barriers, and inequitable access. Psychotherapy represents a biologically active, durable, and skill-based treatment for anxiety disorders. Future research should prioritize precision-based models, digital interventions, culturally adapted therapies, and scalable implementation strategies to reduce global treatment disparities and optimize personalized care.
Keywords: Psychotherapy; Anxiety Disorders; Cognitive Behavioral Therapy; Exposure Therapy; Treatment Gap; Digital Mental Health